Political parties and citizens' well-being among non-democratic developing countries. (November 2021) - Bellinger, Nisha
This article explains variations in citizens' well-being among non-democratic developing countries by disaggregating non-democracies and focusing on the role of party strength. The effect of party strength is analyzed through the prisms of information and capacity . I argue that stronger parties facilitate a two-way flow of information between citizens and political leaders about societal needs. Additionally, stronger parties have the capacity to aggregate information and formulate policies that meet the needs of the citizenry. The theory is tested through a time-series-cross-sectional analysis of developing non-democracies and is supplemented with a case narrative on Rwanda. The findings demonstrate the significance of disaggregating non-democratic regimes to better understand the political dynamics of citizens' well-being.